Credit Risk of Banks in Africa: Determinants and Impact of Credit Risk on Banks’ Lending Rate and Bank Stability. - Appiah, M.A.F. (University of Ghana, 2015)
Purpose – This research is to identify the determinants of credit risk of banks in Africa and examine the impact of credit risk on banks’ lending rates and banks’ stability. Design/methodology/approach – This study considers 197 banks across 29 countries in Africa over the period 2008-2012. Africa was divided into three income brackets according to the 2010 World Bank classification. A large sample of 197 banks was used in order to have enough banks in each income bracket. Sampling was done focussing on the banks and not countries. Multiple regressions were specified and estimated using the Prais –Winstein estimation technique. This estimation technique was adopted due to the heteoroscedatic and serially correlated errors of the traditional generalized least squares technique. Findings – The results of the study suggests that the predictive power of bank specific and macroeconomic variables on credit risk differs among the income brackets within which the bank operates. Credit risk was also found to have an impact on lending rates only in the low income bracket and has an impact on bank stability only in the low middle income bracket. Credit risk however has no impact on banks’ average lending rate and banks stability in the upper middle income bracket. Originality/value – This study, to the best of the knowledge of the author, is the first to consider credit risk in banks and its impact on lending rate and stability in Africa by considering the three income brackets separately. This is important since Africa is not a homogenous unit and countries within the continent have different levels of income and development. Policy makers and bank managers therefore should consider this study so as not to go in for inapplicable policies and regulations towards credit risk, lending rates and stability of banks. Keywords: Credit risk, Lending rates, Bank stability, Africa, Income bracket.
Thesis (MPhil.) - University of Ghana, 2015